ADVENTURE ACTIVITIES AS A CONTENT IN PHYSICAL EDUCATION: A NEW PROPOSAL TO SCHOOLS. (Fiep Bulletin - online, 2019)
Aims: School physical education, based on the body culture of movement, contributes with its different contents for the formationof critical citizens and adventure activities, can be more a possibility of teaching and learning that have a relation with modernityand a new conception of human movement. Methodology: Bibliographic review by subject. They were used as references,projects and periodicals published between the years of 1997 to 2015. Objectives: Discussing the possibility of using adventureactivities as content in school physical education classes, bringing the proposal for the formation of the subject and the culturebody of movement, autonomy and citizenship. Conclusion: The inclusion of adventure activities in school is justified by itsmodalities and its guiding axis is the practices of teachers in schools; The National Curricular Parameters favor and point to theneed to enrich and broaden the experiences provided by the various contents of the body culture of movement that bring with itaffective, cognitive, psychomotor and socio-cultural dimensions to the students, besides providing leisure, tourism, the joy andsatisfaction of experiencing something different, innovative and with characteristics of self-improvement, self-control and wellbeingexperienced in nature.
Keywords: education; adventure activities; body culture of movement; school physical education